DAMPAK PORNOGRAFI TERHADAP PERKEMBANGAN PERILAKU REMAJA - Siti Fatimah (INSTITUT KESEHATAN DELI HUSADA, 2022)
Adolescence is a period of transition from childhood to adulthood with an age range of 12-22 years, during which a maturation process occurs, both physical and psychological. According to WHO, anemia is the biggest nutritional problem in adolescents which can have a negative impact on their performance and cognitive growth. Increased knowledge through a health education approach is an activity to provide and improve cognitive, affective to individuals in this case young women in order to maintain and strengthen their own health. Health education about anemia in young women can provide knowledge about nutrition in adolescents in order to prevent anemia in young women. Exposure to pornography in children is mainly obtained through the internet which is exacerbated by